2018
DOI: 10.1111/jopr.12800
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Adaptation of CAD/CAM All‐Ceramic Crowns Made by Different Impression Methods: A Literature Review

Abstract: All-ceramic crowns for teeth are widely used for restoring teeth. Stone casts have been made from conventional impression methods; however, newer techniques have made this process easier and faster for both the patient and the practitioner. Laboratory CAD/CAM technology mainly involves scanning the die stone, while other systems permit impression or intraoral scanning; however, one major concern remaining is the marginal fit of the restorations made using different methods for recording the prepared teeth. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 59 publications
(181 reference statements)
1
46
1
4
Order By: Relevance
“…However, Nakamura et al, reported differences in adaptation according to the configuration of the abutment tooth. The tooth preparation, scanning and analyzes was made by one operator and, then, duplicated in order to avoid creates variation operator . Cementation was not performed since the objective was to evaluate before and after crystallization process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Nakamura et al, reported differences in adaptation according to the configuration of the abutment tooth. The tooth preparation, scanning and analyzes was made by one operator and, then, duplicated in order to avoid creates variation operator . Cementation was not performed since the objective was to evaluate before and after crystallization process.…”
Section: Discussionmentioning
confidence: 99%
“…However, other factors were considered and evaluated, such as: the molding techniques, ceramic material, the technological innovation by the dental community with increasing as in the CAD / CAM system, and TR and microCT . The CEREC system selected has been a positive result in literature when compared with other CAD/CAM systems . However, changes continue to happen in newer scanners and software .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both processes have specific advantages and disadvantages. The conventional procedure is based on decades of experience and refined procedures, though mistakes still occur in the context of implant dentistry, such as displacement of scan abutments or dental stone expansion . The digital workflow has advantages in reproducibility and quality standardization, but one main disadvantage is that deviations in the digital impression can lead to clinically unacceptable errors …”
mentioning
confidence: 99%
“…Im Folgenden soll die Genauigkeit als Basis und Hilfe bei der jeweiligen Indikationsstellung dienen.Festsitzende ProthetikEinzelzahnversorgungenFür Inlays, Onlays, Teil-oder Vollkronen liefern Intraoralscanner heute klinisch gute Werte, dies nicht nur vor dem Hintergrund der Randschlussgenauigkeit, sondern ebenfalls in Bezug auf die Dimensionstreue der jeweiligen Gerüste. Hierbei sind klinische Genauigkeiten von < 100 µm möglich[2,3].…”
unclassified